Ships / illustrated by Jonothan Potter. - Butterfield, Moira, |d 1961; a Potter, Jonothan, |e ill. (London ; New York : Dorling Kindersley :Houghton Mifflin Co, 1994)
SEE INSIDE 10 FASINATING VESSLES
age 4-10
Keywords: Naval architecture--Juvenile literature; Ships--Charts, diagrams, etc.--Juvenile literature; Seafaring life--Juvenile literature; Ships; Seafaring life